2007
DOI: 10.1159/000106472
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Self-Reported and Observer-Reported Ratings for Psychopathology in Psychiatric Inpatients

Abstract: Objective: Psychopathology can be measured adopting the perspective of clinicians or the perspective of patients themselves. In the present study, we investigated the degree of coherence between these two viewpoints. Methods: During an 8-month recruitment period, all consecutive patients admitted to two Italian residential facilities were screened for inclusion. The 24-item version of the Brief Psychiatric Rating Scale-Expanded Version (BPRS-E) and the Brief Symptom Inventory (BSI) were administered within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…In support of our hypothesis, SPQ subscale scores were significantly associated with their corresponding clinician-rated SIDP item scores for cognitive-perceptual (positive) schizotypal traits in both groups. This result is consistent with studies in schizophrenia suggesting that self-reported positive symptoms corresponded well with clinician ratings (Hamera et al, 1996;Lincoln et al, 2010;Liraud et al, 2004), although some studies have failed to find such correlations for positive symptoms (Biancosino et al, 2007;Morlan and Tan, 1998). Positive schizotypal traits may be more accurately self-reported as the SPQ asks about these items directly (e.g., "Do you sometimes feel that things you see on the TV or read in the newspaper have a special meaning for you?…”
Section: Discussionsupporting
confidence: 88%
“…In support of our hypothesis, SPQ subscale scores were significantly associated with their corresponding clinician-rated SIDP item scores for cognitive-perceptual (positive) schizotypal traits in both groups. This result is consistent with studies in schizophrenia suggesting that self-reported positive symptoms corresponded well with clinician ratings (Hamera et al, 1996;Lincoln et al, 2010;Liraud et al, 2004), although some studies have failed to find such correlations for positive symptoms (Biancosino et al, 2007;Morlan and Tan, 1998). Positive schizotypal traits may be more accurately self-reported as the SPQ asks about these items directly (e.g., "Do you sometimes feel that things you see on the TV or read in the newspaper have a special meaning for you?…”
Section: Discussionsupporting
confidence: 88%
“…As we found statistically significant correlations with both positive and negative symptoms, our results do not confirm earlier findings of Hamera et al 9 and Preston and Harrison, 10 according to whom negative symptoms are more difficult to be accurately reported than positive symptoms, but support earlier findings of Bell et al 12 and Liraud et al 11 The lack of association between scales measuring affective symptoms stands in contrast to previous studies which reported good agreements in this dimension. 1,15 With regard to the moderating influence of the disease stage, we could not confirm that the association between self-rating and observer-rating is higher in ARMS than in FEP patients. However, when P-values were not corrected for multiple testing, there was one significant interaction which was in the opposite direction of what we had expected.…”
Section: Discussionmentioning
confidence: 61%
“…poor insight, denial, delusions, cognitive deficits) that could hinder an accurate self‐rating of their symptoms, it has long been assumed that self‐ratings – especially of positive psychotic symptoms – are unreliable in these patients . However, our literature research revealed that at least six studies found a good agreement between self‐rating and observer‐rating of positive psychotic symptoms in psychosis patients and only three studies found poor correlations …”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations